Grain refinement and abnormal peritectic solidification in WxNbTiZr high-entropy alloys. (December 2022) - Shen, Z.D.; Ma, Z.L.; Xu, Z.Q.; Cheng, X.W.
Graphical abstract: Highlights: Peritectic high entropy alloys (PHEAs) are proposed and explored. High growth restriction factor and primary phase segmentation lead to grain refinement. Sufficient peritectic transformation and pearl chain structures are revealed in PHEAs. Peritectic solidification can simultaneously enhance the strength and ductility. Abstract: The microstructures of many high-entropy alloys (HEAs) can be understood or controlled based on traditional phase formation mechanisms. In this study, peritectic solidification was introduced to HEAs by designing novel W x NbTiZr peritectic high-entropy alloys (PHEAs). The phase constitutions and solidification microstructure evolutions of W x NbTiZr were clarified by combining experiments and thermodynamic simulations. Grain refinements were achieved in W x NbTiZr, which should attribute to the high growth restriction factors introduced by W solute and the segmentations of the primary phase during peritectic transformation. The significantly refined grains can simultaneously enhance the strength and ductility of the alloy. High fractions of peritectic phases and special pearl chain structures that are highly likely the products of peritectic solidification are seen in W x NbTiZr but not in the typical binary W-Zr peritectic alloy, highlighting that the compositional complexity featured by PHEAs could heavily influence peritectic reaction. The PHEAs idea is also generalized by developing W x MoTiZr alloys.